UK health spending - George Stoye; Ben Zaranko (Institute for Fiscal Studies (IFS), 2019)
Funding the National Health Service is the biggest single thing the government does, so it is not surprising that it is at the forefront of the election campaign. In this report, we look at how health spending has changed over the last 70 years and place funding increases since 2010 in the context of the pressures associated with an ageing population. We then compare existing spending plans for the NHS to those implied by the political parties' manifestos at the 2017 general election and examine capital spending on the health service. Finally, we consider the longer term outlook for health spending.
Keywords: 330; Gesundheitskosten; Prognose; Großbritannien